Politicians' social welfare criteria: An experiment with German legislators - Sandro Ambuehl; Sebastian Blesse; Philipp Doerrenberg; Christoph Feldhaus; Axel Ockenfels (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
Much economic analysis derives policy recommendations based on social welfare criteria intended to model the preferences of a policy maker. Yet, little is known about policy maker's normative views in a way amenable to this use. In a behavioral experiment, we elicit German legislators' social welfare criteria unconfounded by political economy constraints. When resolving preference conflicts across individuals, politicians place substantially more importance on least-favored than on most-favored alternatives, contrasting with both common aggregation mechanisms and the equal weighting inherent in utilitarianism and the Kaldor-Hicks criterion. When resolving preference conflicts within individuals, we find no support for the commonly used "long-run criterion" which insists that choices merit intervention only if the lure of immediacy may bias intertemporal choice. Politicians' and the public's social welfare criteria largely coincide.
Keywords: C9; D6; 330; Positive welfare economics; politicians; preference aggregation; paternalism